Effect of Cam Profile On Cylinder Pressure In Revetec Engine - Maisara Mohyeldin, Gasim Mohamed; Amirruddin, Abdul Kadir (2010)
Revetec engine is a new engine arrangement used to increase engine’s efficiency by replacing the crankshaft and the connecting rod used in conventional engines by cams to control the piston movement. Cam profile contributes great effect in combustion characteristics, so it is very important to find the suitable cam profile to achieve the maximum cylinder pressure. In this paper a computational work was created to make a comparison between three types of cam profiles, which gives a specific motion for the piston, mainly: simple harmonic, constant acceleration and Cycloidal motion; In order to calculate the cylinder pressure during compression and combustion strokes. Results showed that by using cam with constant acceleration motion profile, the maximum cylinder pressure has increased with 7 %, and with the Cycloidal motions the increase in maximum cylinder pressure reaches 14 %, compared with simple harmonic motion, at the same compression ratio and heat addition. The result obtained from this study has shown that by using a cam profile, with which Cycloidal motion was applied to the piston, the cylinder pressure can be increased.